SYNTHESIS OF ZINC OXIDE/CHITOSAN/CHITRONELLA ESSENTIAL OIL HYBRID NANOPARTICLES USING SOL-GEL METHOD: STRUCTURAL AND OPTICAL PROPERTIES - Astuti, Budi; Hasni, Nur 'Ainiyyah; Sulistiyo Rini, Ari; Mohamad Ayubi, Dimas; Yulianto, Agus; Masturi, Masturi; Darsono, Teguh; Marwoto, Putut; Sugianto, Sugianto; Abu Bakar, Suriani; Fatiatun, Fatiatun (Universitas Mataram, 2025)
Due to their properties, ZnO nanoparticles have recently been used as an additive material in active food packaging. ZnO has a wide band gap of about 3.37 eV, making it effectively used under UV light. However, ZnO nanoparticles are not effectively used under visible light. This study successfully synthesized ZnO-Chitosan-Citronella Essential Oil hybrid nanoparticles using sol-gel methods. Adding chitosan and citronella essential oil will affect nanoparticles' structural and optical properties. The structural, morphological, and optical properties of characterized hybrid nanoparticles were studied using X-ray diffraction (XRD) and FTIR, scanning electron microscope (SEM), energy dispersive X-ray (EDX), and UV-Vis spectroscopy. From XRD, it was obtained that the ZnO nanoparticles produced have a hexagonal wurtzite crystal structure with angles of 2q = 31.76°, 34.48°, 36.30° which are crystal planes with orientations (100), (002), and (101), as well as several other peaks for planes (102), (110), (103), (200) and (112) with a crystallinity index value of 86.5390%, and crystallite size of 8.87nm and 7.5335 nm. From FTIR Characterization, Zn=O functional groups were also obtained at wave numbers 657 and 475 cm-1. The morphology of ZnO nanoparticles from SEM spectroscopy shows a spherical shape with agglomeration, and the composition of the components Zn, O, and N elements is found, which come from chitosan materials. Furthermore, from the UV-Vis spectroscopy characterization, it was obtained that the absorption occurred in the 380-600 nm region with a band gap energy of 3.25 eV (using the tauc plot method), which was slightly different from the empirical results of 3.30 eV. The results show potential future studies of hybrid nanoparticles, such as additive materials in active food packaging.